Regional diversity in growth performance in China. (1st January 2012) - Hicks, John; Basu, P.K.; Sappey, Richard B.
At the national level, China's amazing growth has been driven by increases in labour productivity. Initially, this was explained by increases in the capital/labour ratio, but, more recently, increases in total factor productivity (apparently as a result of increased spending on education) have become a more important part of the explanation. This paper examines the growth experience at the provincial level and finds it to have been very uneven with the East generally growing earlier than the West. Notwithstanding this, the data suggests that growth in all provinces tends to pass through the same stages. Initially, labour productivity increases because of the growth in capital and, later in the process, growth is maintained because of improvements in TFP emanating from improvements in education. We identify that an appropriate policy measure to assist in achieving balanced growth across the provinces is to continue to increase educational expenditures in the lagging provinces.